The influence of concomitant diseases on a long-term prognosis in patients with chronic ischemic heart disease according to the PROGNOZ IBS register - S. N. Tolpygina; S. Yu. Martsevich; A. D. Deev (Столичная издательская компания, 2015)
Aim. To study the incidence of comorbidities and their impact on the prognosis in patients with ischemic heart disease (IHD) included into the PROGNOZ IBS Register. Material and methods. Data from the PROGNOZ IBS register of patients diagnosed with IHD using coronary angiography during the reference hospitalization (n=541; 432 male and 109 female) was included in the analysis. 504 (93%) patients were included in the survival analysis. Risk factors of cardiovascular diseases, associated with atherosclerosis, or those that were complications of IHD were considered as comorbidities as well as not cardiovascular diseases - chronic obstructive pulmonary disease, bronchial asthma and chronic kidney disease (CKD). Results. The average duration of follow-up was 7.3±2.19 years. The average number of comorbidities in patients with IHD was 1.83. Comorbidities worsened the prognosis of life: the presence of diabetes mellitus (DM) increased the relative risk (RR) of primary endpoint occurrence by 1.7 times, the combination of DM with hypertension - by 2.4 times, a history of stroke - by 2.3 times (p<0.05); 2 and 3 heart diseases - respectively, by 2.3 and 3.2 times (p<0.05); a combination of chronic lung diseases and CKD stages 3-5 - by 1.4 times (p=0.06); the presence of 2, 3, 4 and 5 comorbidities - respectively, by 4, 5, 6.4 and 13 times (p<0.001). The risk of death from all causes was determined by the number of concomitant cardiovascular diseases: 2 diseases increased RR by 2.3 times, 3 diseases - by 4.6 times, a combination of any 4 diseases - by 3.5 times, of 5 diseases - by 5 times (p<0.05). Conclusion. Prognosis of life in IHD patients is worsened by the presence of several comorbidities: risk factors of cardiovascular disease (DM and hypertension), cardiovascular diseases associated with atherosclerosis or those that are complications of IHD, chronic lung diseases and CKD.